(untitled) (TAMADDUN NURI JURNALI, 2024)
The article discusses the transformation of ecological culture and religious values, changing their attitude towards the environment and mother nature in a positive way, eliminating global environmental problems and their negative consequences, including the lack of water resources, global climate changes.